Black soldier fly larvae (Hermetia illucens) frass and sheddings as a compost ingredient - Jasso, Beatrice; Quinchia, Luisa; Waliczek, Tina M.; Drewery, Merritt L. (Frontiers in Sustainable Food Systems, 2024)
One of the byproducts from rearing Black soldier fly larvae (BSFL) is its excrement, referred to as frass, and sheddings. As the commercial insect rearing industry is emerging in the U.S., thereis not yet an established market for frass although the yield often exceeds that of BSFL by twoto three-fold. It has been suggested that frass could be converted into compost; however, there is a lack of literature investigating the effect of frass and larval sheddings inclusion on final compost quality. Accordingly, the objective of this study was to determine if BSFL frass and sheddings are a viable compost ingredient with the overarching purpose of identifying a potential market for an otherwise waste product of the insect-rearing industry. To address this objective, four experimental compost piles (6.12 m 3 each) with increasing levels of BSFL frass and sheddings (18.75%, 22.87%, 27.13%, 31.25%) were developed. Across piles, wood chips (37.50%) and unscreened compost (18.75%) were consistent and frass and sheddings displaced food waste. Piles were mixed and tested for moisture and temperature weekly. Once internal temperatures decreased to 38°C, piles cured until internal temperatures were consistently <32°C.After curing, samples were collected from each pile and analyzed for pH, macro-and micronutrients, particle size, stability, and maturity. The entire composting process, including two months of curing, required five months. For each pile, pH, nitrogen, carbon, carbon:nitrogen, and potassium were within optimal ranges. Further, stability, measured as mg CO2-C/g solids/day, and maturity, measured as seed emergence and seedling vigor, were also within optimal ranges. However, moisture/solids; organic matter; phosphorus; and stability, measured as mg CO2-C/g organic matter/day, were out-of-specification for each pile given compost quality tests. Our findings indicate BSFL frass and sheddings may be a viable compost ingredient, but further research is recommended to establish optimal inclusion levels to maximize finished compost quality.